Progress in the Formulation, Evaluation, and Execution of Investment Projects in the Public Sector of Peru - Martínez Ccallata, Raúl (2025)
This study carries out an analysis of progress and improvements in investment in projects in the public sector of Peru between the years 2001 and 2022. To do this, descriptive statistics were carried out on the main characteristics of investment in the public sector and interviews with the sectorists of the General Directorate of Multiannual Investment Programming (DGPMI) of the Ministry of Economy and Finance (MEF). The research methodology is qualitative, since a brief account is made of some research concerning the topic of investment in the public sector in the Formulation and Evaluation (M&E), and Execution stage; Likewise, semi-structured interviews were carried out with the Transportation, Agriculture, Sanitation, Education and Health sectors of the DGPMI of the MEF. The main results of this research are the following: the viability time of the projects was reduced through the use of technical sheets; There are fewer cases of duplication of project investment given the best control techniques in the Investment Bank, for example GeoInvierte, and information alerts.